TUTURAN IMPERATIF BAHASA BATAK TOBA DALAM UPACARA ADAT KEMATIAN - Ipanilidia Nababan; Dudung Burhanudin; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The imperative sentence can range from having to do something until the prohibition to do something. The imperative sentences contained in the Batak Toba language can range from very harsh or rough errands to very subtle or polite requests. Thus it can be said that the imperative sentences in Batak Toba language are complex and varied. Based on the formulation of the problem, this study aims to describe the form and meaning of imperative speech in traditional ceremonies of Batak Toba death. This study used descriptive qualitative method. Data analysis is done by identifying data based on the form and meaning of imperative speech, classifying each data that has been identified based on the form and meaning of imperative speech, describing the data that has been classified, the interpretation of conclusion, which is concluding from the data that have been obtained since the beginning until the end of the study. The results of the study found that: (1) There are only five forms of imperative speech, namely: ordinary imperative, demand imperative, permit imperative, imperative invitation, and imperative of the order is in the Toba Batak Toba (2) Traditional Ceremony Of four meanings of imperative speech, two meanings of speech that is meaningful madness and meaningful hope. Whereas the two meanings of other imperative speeches are: meaningful messenger and meaningful prohibition, not found.Key words: Imperative, Batak Toba Language